Supporting authors in documenting and sharing operative knowledge. Issue 4 (13th August 2018) - Rossi, Davide; Di Iorio, Angelo
Abstract : Purpose: The purpose of this paper is to design and evaluate an authoring tool to support users in documenting knowledge using social software-based platforms in order to improve information sharing within organizations. Facilitating the creation of such content has been identified as a critical point for the acceptance of similar platforms. Design/methodology/approach: The authors propose a general framework to design and assess technological solutions that positively affects users' contribution – and, as a consequence, users' engagement – when knowledge is externalized, made persistent and shared by using semantic wikis. The definition of the framework has been derived from a case study on operational knowledge management. This framework revolves around interaction with actual users for both design and evaluation. The latter exploits usability tests based on the System Usability Scale and analysis based on the grounded theory. Findings: The framework proved to be effective when applied for a solution for the authors' case study. The results of the designed tool were well accepted, and the tool was characterized by its users as having high usability. A limitation that emerged is related to the ability to support authors not just in creating documentation but also in maintaining it, an aspect that needs to be better addressed in the future. Originality/value: The presented framework can be instantiated for similar platforms and provides a common ground for assessment of tools. The produced tool significantly simplifies the production of documentation related to community best practices. Valuable user feedbacks were collected about possible improvements for tools supporting authors.